The End and the Beginning:: chance and poetics of listening in Eduardo Coutinho - Fischer, Rosa Maria Bueno (Revista Brasileira de Estudos da Presença, 2024)
This text discusses the pleasure of filming and researching, focusing on the documentary The End and the Beginning, by Eduardo Coutinho. The aim is to articulate affirmations by the director about his creative process, with scenes and statements from the people interviewed in the film, most of whom are over 80 years old. In dialogue with Didi-Huberman, Foucault, Rancière, and Marie José Mondzain, as well as partners of Coutinho such as Jordana Berg, João Moreira Salles, and Consuelo Lins, issues related to the craft of academic research are discussed: the relations between truth and montage, real and imaginary, listening to the other and poetry of the word, image and ethical commitment.